The Influence of Fixed Assets Investment, Solvency, Working Capital and Free Cash Flow on The Profitability of Manufacturing Companies Listed on The Indonesian Stock Exchange Period 2017-2020 - Wibowo, Arief Nugroho; Pangesti, Indah; Saputro, Firdaus Budhy (Economics and Business Journal (ECBIS), 2024)
This research aims to examine the effect of Fixed Asset Investment, Solvency, Working Capital and Free Cash Flow on Profitability. Several previous studies showed various results. To obtain valid results, a test is carried out on each variable based on the hypothesis that is built. The research population is manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sample used was selected using a purposive sampling method. After eliminating data with several criteria, 57 companies were identified as samples during the 2017-2020 period. Hypothesis testing was carried out using multiple linear regression analysis with the help of IBM SPSS version 25 software. The results of this research show that Fixed Asset Investment, Solvency and Free Cash Flow have an influence on Profitability, while Working Capital has no influence on Profitability.